STUDI PERSEPSI DAN NIAT PEKERJA LAPANGAN DALAM MELAPORKAN KEJADIAN BERBAHAYA DAN KECELAKAN DI TERMINAL PETIKEMAS SEMARANG - Nuralmasdini Winnaputri; Hanifa Maher Denny; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Reporting any hazardous events and accidents at workplace is one of safety behavior that can reduce the occurance of the accident. Hazardous events consist of unsafe actions and unsafe conditions. Semarang Container Terminal is a container service company that has a potential of dangerous events and accidents. This research is a qualitative research with the aim to assess the perception and intentions of field workers in reporting the hazardous events and accident in Semarang Container Terminal based on the Theory of Planned Behavior. Data obtained using the technique of indepth interview and observation. The main informants in this study were 17 field workers, consisted of 6 RTG operators, 2 field foreman, 6 tally man, and 3 head truck operators. The triangulation informants were consist of 1 Manager of Safety and Security Management, 1 Assistant Manager of Operational Division and 1 Supervisor of Loading and Unloading. The results showed that all of field workers already have a good perception and intention to report the unsafe conditions and accidents while 82.4% of them did not have a good perception and intention to report the unsafe actions. Some of them  already had sufficient knowledges of hazardous events and accidents. Although some of them  have experienced or found dangerous events and accidents, but not all of them agree to report unsafe action. Some of them had a good subjective norm but didn’t have a good perceived behavioral control in reporting unsafe action.